2011
DOI: 10.1016/j.virusres.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity and potential recombination events in the coat protein gene of Apple stem pitting virus

Abstract: SUMMARYThe variability of the Apple stem pitting virus (ASPV) coat protein (CP) gene was investigated. The CP gene of ten virus isolates from apple and pear trees was sequenced. Comparison of all sequenced virus isolates revealed high diversity of the CP gene (70.7-93.5 % at the nucleotide level and 77.8-98.7 % at the amino acid level). Additionally, one or two deletions in the N-terminal part of the coat protein gene of the studied virus isolates were identified. The ratio of nonsynonymous to synonymous polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
5
23
0
3
Order By: Relevance
“…The estimation of selection pressure on the ACLSV genome fragments revealed that they undergo the strong negative selection. Studies conducted in different countries showed that purifying selection dominates in the cases of viruses infecting apple trees, but individual nucleotides or viral genome regions may be under positive selection (Komorowska et al 2011;Liebenberg et al 2012;Liu et al 2014;Yoon et al 2014). Perhaps, the negative selection pressure can be explained by the participation of a single viral protein in numerous processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of selection pressure on the ACLSV genome fragments revealed that they undergo the strong negative selection. Studies conducted in different countries showed that purifying selection dominates in the cases of viruses infecting apple trees, but individual nucleotides or viral genome regions may be under positive selection (Komorowska et al 2011;Liebenberg et al 2012;Liu et al 2014;Yoon et al 2014). Perhaps, the negative selection pressure can be explained by the participation of a single viral protein in numerous processes.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, such a pattern is formed by the action of strong purifying selection which is typical for plant viruses. Similarity between isolates from the same host plant is observed much more frequently, although it is not always (Komorowska et al 2011;Liebenberg et al 2012;Liu et al 2014;Valasevich et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Однако четкой картины распределения образцов в зависимости от места отбора пробы выявить не удалось, несмотря на значительную вариабельность вирусных геномов (Liebenberg et al, 2012;Liu et al, 2014). Кластеризация изолятов в зависимости от растения-хозяина наблюдается чаще, хотя и она не является абсолютной (Komorowska et al, 2011;Liebenberg et al, 2012;Liu et al, 2014). Выявленная нами генетическая дифференциация вирусов ACLSV, ASPV и ASGV также не связана непосредственно с реги-оном их распространения (см.…”
Section: Discussionunclassified
“…Результаты других исследований также свидетельствуют о значитель-ном генетическом разнообразии этих вирусов. Степень идентичности генов, кодирующих белок оболочки ASPV у изолятов, полученных в Польше, составляла 70,7-93,5 % (Komorowska et al, 2011). Последовательности двух геномов ACLSV, выделенных на территории Китая, имели степень идентичности 95,1 % (Niu et al, 2012).…”
unclassified
See 1 more Smart Citation